Um método para a realização do inventário florestal suprimindo a cubagem rigorosa - Cabacinha, Christian Dias (2003)
The purposes of this study were to examine the application of the profile functions (taper) and the hypsometric relationship to estimate the diameter at relative height and to test the geometric methodology to estimate individual tree volumes. The data base is from 48 sample units of 360 m2, totalizing 1819 tree of a clonal plantation (hybrid of Eucalyptus grandis and Eucalyptus urophylla), with 6,5 years old, from 3 sites. The property belongs to Aracruz Celulose S.A., located on Brazilian east region. In each sample unit was measured the dbh of each tree, the total height and the diameter in the relative height ((ht-2)/2) of the three central sample unity lines. The second diameter measurement was taken by using Bitterlich relascop, the Wheller penta-prism and the caliper. The main results were: the use of the taper function and the hypsometric relationship methodology with geometric method generated good volume estimates when the diameter were measured using the caliper; the Prodan and Curtis models generated good height estimates, although the Prodan model must be used just in the interval limits of the data; the Omerod provided excellent diameter estimates for both 0,3 m and (ht-2)/2 height position; the geometric method application, using the diameter taken with the caliper on relative height ((ht-2)/2), provided more accurate results than the traditional inventory; compared to real merchantable volume the geometric method estimates were more precise using the line angular coefficient to estimate the diameter at relative height, the parabola index with support diameter, the modified line angular coefficient for estimate the line angular coefficient, the modified line angular coefficient for estimate the diameter at relative height, the parabola index without support diameter and the line angular coefficient.; among the studied methods the more accurate was the geometric method using the line angular coefficient to estimate the diameter at relative height. All sample size tested provided good results. The size of 5 trees by sample unity was sufficient to provide volume precise estimates.